LABOR FUNCTION OF THE EMPLOYEE UNDER THE LEGISLATION OF UKRAINE: CONTENT AND MAIN ELEMENTS - Дігтяренко, Ганна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
The aim: to consider the content and basic elements of the labor function as a mandatory condition for an employment contract under the legislation of Ukraine. The methods of the research: the main attention is focused on the disclosure of the essence of the labor function of the employee as a mandatory condition of the employment contract through the main elements such as «profession», «speciality», «specialization», «qualification», «position». Discussion: it is substantiated that all structural elements of the labor function are of great importance both for the employee and for the employer, all the elements are closely interconnected and interdependent. Results: it is concluded that the absence of any component leads to a violation of the principle of certainty of the labor function and the terms of the employment contract as a whole.